2018
DOI: 10.1007/s00221-018-5280-9
|View full text |Cite
|
Sign up to set email alerts
|

The sensory origin of the sense of effort is context-dependent

Abstract: The origin of the sense of effort has been debated for several decades and there is still no consensus among researchers regarding the underlying neural mechanisms. Some advocate that effort perception mainly arises from an efference copy originating within the brain while others believe that it is predominantly carried by muscle afferent signals. To move the debate forward, we here tested the hypothesis that there is not one but several senses of effort which depend on the way it is evaluated. For this purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…There is growing evidence that the signals contributing most to the sense of force and effort are task-dependent. For example, Monjo et al [29] found that muscle spindles contribute to the sense of effort when completing a one-arm force matching task but that central and peripheral sources are important when completing twoarm force matching. In contrast to the perception of effort, the sense of muscular force during one-arm [30] and two-arm [31] matching tasks has been commonly attributed to Golgi tendon organs.…”
Section: Potential Mechanisms Contributing To the Force Matching De Citsmentioning
confidence: 99%
“…There is growing evidence that the signals contributing most to the sense of force and effort are task-dependent. For example, Monjo et al [29] found that muscle spindles contribute to the sense of effort when completing a one-arm force matching task but that central and peripheral sources are important when completing twoarm force matching. In contrast to the perception of effort, the sense of muscular force during one-arm [30] and two-arm [31] matching tasks has been commonly attributed to Golgi tendon organs.…”
Section: Potential Mechanisms Contributing To the Force Matching De Citsmentioning
confidence: 99%
“…Peripheral information arises from muscle and cutaneous mechanoreceptors (22, 27). Muscle mechanoreceptors include Golgi tendon organs (2831) and muscle spindles (32, 33), and cutaneous mechanoreceptors include slow-adapting and fast-adapting units (3437). Central information arises from an individual's perceived effort, or the extent to which an individual perceives that their arm muscles are being driven in relation to the maximum.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been confirmed that the sense of effort can be used for judging force/heaviness, an influential current hypothesis predicts that judgments of force/heaviness are based not only on sense of effort but also on feedback of afferent signals returning from the periphery [37]. Monjo et al propose that humans do not perceive signals of only efferent or afferent signals as sense of effort but can perceive effort by changes in weight between both signals according to the experimental conditions [38]. The present experiment did not include conditions such as paralysis of muscle spindles.…”
Section: Discussionmentioning
confidence: 99%